Transformation of U.S. Agriculture - Bohman, Mary (2018)
Mary Bohman SPECIAL EVENT Transforming Agriculture: Experiences and Insights from Brazil and Beyond Co-Organized by IFPRI and Embrapa MAY 15, 2018 - 12:15 PM TO 01:45 PM EDT